2008
DOI: 10.2224/sbp.2008.36.4.483
|View full text |Cite
|
Sign up to set email alerts
|

An Evaluation of Teachers' Views of Primary School Principals' Practice of Democratic Values

Abstract: The purpose of the study was to evaluate teachers' views about the level of practice of democratic values by primary school principals. Participants were 300 primary school teachers from four different regions of Turkey. The data were collected through a questionnaire, and analyzed by using t test and ANOVA tests. Results indicate that gender, educational level, and membership of a union make a difference in terms of practicing democratic values. Furthermore, some meaningful differences were noted in the subdi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 10 publications
(13 reference statements)
0
4
0
7
Order By: Relevance
“…In parallel to this finding, Tunca (2012) also found out that teachers' having certain professional values differed in terms of the seniority variable. Additionally, it was reported that democratic values of elementary education teachers , high school education teachers (Yurtseven, 2003), and administrators (Genç, 2008) varied at sub-dimensions as the seniority variable was concerned. Besides, there are studies in the literature that resulted in organizational values of teachers not varying according to their service years (Zoba, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…In parallel to this finding, Tunca (2012) also found out that teachers' having certain professional values differed in terms of the seniority variable. Additionally, it was reported that democratic values of elementary education teachers , high school education teachers (Yurtseven, 2003), and administrators (Genç, 2008) varied at sub-dimensions as the seniority variable was concerned. Besides, there are studies in the literature that resulted in organizational values of teachers not varying according to their service years (Zoba, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Ta skupina istraživanja odgovara na pitanje zašto je važno razvijati demokratsko školsko vođenje, odnosno koji su njegovi pozitivni efekti te postoje li negativni. Druga skupina istraživanja navodi primjere kako se razvija i provodi demokratsko školsko vođenje (Rusch, 1995;Møller, 2006;Genc, 2008;Jwan, Anderson i Bennet, 2010;Hope, 2012; Mncube, Davies i Naidoo, 2015) te koji su izazovi i problemi koji se pritom javljaju. Posljednja skupina istraživanja istražuje razvoj demokratskih školskih zajednica, no pritom poseban naglasak daje ulozi voditelja škole u tome procesu (Harber i Trafford, 1999;Normore i Jean-Marie, 2008;Kensler i sur., 2009;Jwan, Anderson i Bennet, 2010;Delgado, 2014;Gülbeher, 2016).…”
Section: Istraživanja Demokratskog šKolskog Vođenjaunclassified
“…Skupina istraživanja koja proučava kako razvijati demokratsko školsko vođenje može se svrstati u dvije kategorije: istraživanja koja kao cilj imaju istraživanje karakteristika, stavova i vrijednosti voditelja koji njeguje demokratsko školsko vođenje (Genc, 2008;Rusch, 1995) te studije slučaja koje detaljno opisuju primjere škola koje su razvijale demokratsko školsko vođenje s ciljem boljeg razumijevanja struktura, praksi i vrijednosti u njima (Møller, 2006;Jwan, Anderson i Bennet, 2010;Hope, 2012;Mncube, Davies i Naidoo, 2015). Cilj, metodologija, uzorak i rezultati navedenih istraživanja predstavit će se u nastavku.…”
Section: Kako Razvijati Demokratsko šKolsko Vođenje?unclassified
See 2 more Smart Citations